IMPLEMENTASI METODE WEIGHTED PRODUCT DALAM MEMONITOR GUDANG PENYIMPANAN ROTI BERBASIS INTERNET OF THINGS PADA PLATFORM NODE-RED - Anderias Eko Wijaya; Haris Nurjaman (STMIK SUBANG, 2020)
The weighted Product (WP) method is one method that can be used in the decision-making process to determine the best candidate. In this study, the WP method is used to determine the bread storage for Roti Kuro Subang.Roti Kuro Subang is one of the business units currently engaged in the processing of food products, especially bread. As the business unit develops, a bread storage warehouse is needed. To help the Roti Kuro Subang determine the bread storage warehouse needed a system that can recommend the most suitable bread storage warehouse. The method used in making this system is the Weighted Product (WP) method. This method was chosen because it can provide the best choice from several alternatives. The inclusion of an Internet of Thing (IoT) concept in this study can improve accuracy in determining the value of criteria in several alternatives.The web platform used is Node-red and the database used is MySQL. The results of this study are to provide alternative bread storage that is most suitable for the Roti Kuro Subang.